Traditions and Innovations in the Dynamics of Ethnosocial Organism Development: Problem Statement - Kazbek I. Ashkhamakhov; Roman S. Kozlov (Publishing house "Sreda", 2020)
Authors of the article pay a special attention to the consideration of traditions and innovations in the dynamics of ethnosocial organism development, since the last decade, the blurring of lines of ethnocultural identity on a global scale has become more obvious. Aggressive penetration into the territory of many states by a pro-Western faceless pseudo culture led to a loss of life orientation at the genetic level and the prospects for the existence of most ethnic groups. The aim of work is to search, identify and analyze the main structure-forming principles, the main provisions of which can preserve a unique and inimitable core of ethnocultural organism in a practical application, give a vector of a further more qualitative state. Methods. Using the principles of formal logic, functionalism, and a systematic approach, it was possible to determine the stages of the origin, transformation, and structural integration of cultural innovations in the ethnic environment. Characteristics of each stage from the side of a positive direction as well as a negative one, leading to the degeneration and decay of the ethnocultural system, is presented. As a result of the study, methodological approaches to preserving ethnic cultures, based on traditional ties in relations within the people were identified. These principles are, in authors' opinion, invariable mechanisms of the dynamic, progressive development of any ethnic group, if the ethnocultural identity of all mankind is perceived as a conscious, creative way for the development and preservation of an ethnos.